Thermal analysis and thermal regulation of photovoltaic thermal system using serpentine tube absorber with modified multi-walled carbon nanotubes enhanced PCM - Rajamony R.K.; Paw J.K.S.; Pandey A.K.; Suraparaju S.K.; Sofiah A.G.N.; Tak Y.C.; Pasupuleti J.; Samykano M.; Abed A.M.; Kiong T.S.; Soudagar M.E.M. (Springer Science and Business Media B.V., 2025)
Abstract: The concept of photovoltaic thermal (PVT) systems holds the potential to reduce global energy consumption by simultaneously generating electricity and heat. However, the widespread adoption of these systems is impeded by technical challenges, particularly the rise in panel temperature and constraints on operation during night hours. The present research aims to explore the effect of coolant flow rate and solar radiation on the electrical output and thermal output of PV, PVT, salt hydrate integrated PVT system (PVT-SH), and modified multi-walled carbon nanotubes infused salt hydrate integrated PVT (PVT-SHMM) systems. Additionally, the study examines the heat transfer analysis of a fabricated PVT system incorporated serpentine flow thermal absorber and modified multi-walled carbon nanotubes infused salt hydrate phase change materials (PCMs). In this experiment, water was used as a cooling fluid, with a flow rate of 0.008 to 0.023 kgs?1 and irradiation of 400 to 800 Wm?2. The findings show that the thermophysical properties of formulated nanocomposite have significantly improved, and the thermal conductivity of nanocomposites improved up to 97.2% compared to pure salt hydrate. The pressure drops enhancement increases become more pronounced at the higher mass flow rate, primarily because of the outlet's elevated viscosity of the cooling fluid. As the water flow rate increases, the heat removal factor exhibited 1.06 times rise, with relatively lower values in turbulent flow regions than in laminar flow conditions. Furthermore, the investigation notes a substantial decrease in panel temperature, an increase in electrical power with higher flow rates, and a higher heat gain at lower flow rates. Thus, the experimental findings confirm that integrating SH and SHMM into the PVT system significantly enhances its performance, allowing stored heat energy to be utilized during periods of unavailable solar energy. ? Akadmiai Kiad, Budapest, Hungary 2024.